Exposure to anticholinergic and sedative medication is associated with impaired functioning in older people with vertigo, dizziness and balance disorders—Results from the longitudinal multicenter study MobilE-TRA - Katzenberger, Benedict; Koller, Daniela; Strobl, Ralf; Kisch, Rebecca; Sanftenberg, Linda; Voigt, Karen; Grill, Eva (Frontiers in Pharmacology, 2023)
Introduction: Anticholinergic and sedative (AS) medication is prescribed for various conditions in older patients. While the general association between AS medication and impaired functioning is well established, its specific role in older individuals with vertigo, dizziness, and balance disorders (VDB) is still incompletely understood. The objective of this study was to investigate, whether an exposure to AS medication is associated with lower generic and lower vertigo-specific functioning in older patients with VDB. Methods: Data originates from the longitudinal multicenter study MobilE-TRA with two follow-ups, conducted from 2017 to 2019 in two German federal states. Exposure to AS medication was quantified using the drug burden index (DBI). Generic functioning was assessed by the Health Assessment Questionnaire Disability Index, appraising the amount of difficulties in performing activities of daily living (ADL). Vertigo-specific functioning was measured using the Vestibular Activities and Participation (VAP) questionnaire, assessing patient-reported functioning regarding ADL that are difficult to perform because of their propensity to provoke VDB (Scale 1) as well as immediate consequences of VDB on activities and participation related to mobility (Scale 2). Longitudinal linear mixed models were applied to assess the association of exposure to AS medication at baseline and the level of generic and vertigo-specific functioning status over time. Results: An overall of 19 (7 from Bavaria) primary care physicians (mean age = 54 years, 29% female) recruited 158 (59% from Bavaria) patients with VDB (median age = 78 years, 70% female). AS medication at baseline was present in 56 (35%) patients. An exposure to AS medication at baseline was significantly associated with lower generic functioning (Beta = 0.40, 95%-CI [0.18; 0.61]) and lower vertigo-specific functioning (VAP Scale 1: Beta = 2.47, 95%-CI [0.92; 4.02] and VAP Scale 2: Beta = 3.74, 95%-CI [2.23; 5.24]). Conclusion: Our results highlight the importance of a close monitoring of AS medication use in older patients with VDB. When feasible, AS medication should be replaced by equivalent alternative therapies in order to potentially reduce the burden of VDB.